Ecology and sexual conflict drive the macroevolutionary dynamics of female-limited color polymorphisms in damselflies - Beatriz Willink; Tammy Ai Tian Ho; Erik I. Svensson (Proceedings of the National Academy of Sciences, 2025)
Sexual conflict over mating has been documented in many species, both in the field and in experimental studies. In pond damselflies (family Coenagrionidae), sexual conflict maintains female-limited color polymorphisms, with one female morph typically being a male mimic. However, it is not known whether sexual conflict can also explain the evolutionary origin of novel female morphs, and if so, what ecological factors play a role in this macroevolutionary transition, by modulating the strength of the conflict. Here, we use phylogenetic comparative methods to show that female color polymorphisms are more likely to evolve in temperate regions and open landscapes, whereas region and habitat shifts are independent of female-color states. We also show that these macroecological patterns are mediated by population densities at breeding sites. Temperate and open habitats are associated with female-polymorphic lineages because they harbor higher densities of adults, promoting more frequent encounters between females and males. Finally, we found that female-limited polymorphisms typically evolve from sexually dimorphic ancestors through the addition of a male-like female morph, consistent with the hypothesis of selection for male mimicry. We conclude that female color polymorphisms evolve in a predictable fashion and are likely driven by ecological conditions that increase the rate of premating interactions and thus the intensity of sexual conflict.